A comparative study of isolation performance of electric automobile seat's suspension added by negative-stiffness structure models. (February 2023) - Li, Shiming; Li, Haitao; Zhang, Li; Wang, Xiangjie
To evaluate the isolation performance of the negative-stiffness structure (NSS) used by the tuned-mass-damper (NSS-TMD) and the air pistons (NSS-AP) on improving the ride quality of the electrical automobile (EA), an EA's dynamics model is built under the excitation of the road surface roughness and the in-wheel-motor. Based on the root mean square value of the driver's seat acceleration response used to assess the driver's ride quality, two models of the seat suspension added by NSS-AP and NSS-TMD are then simulated to compare the performance between NSS-TMD and NSS-AP in enhancing the ride quality of the EA. The study indicates that both NSS-TMD and NSS-AP added to the seat suspension improve the driver's ride quality better than the seat suspension without the NSS. Particularly, the root mean square value of the driver's seat acceleration with the NSS-AP is smaller than that of NSS-TMS by 17.2%. Additionally, when the EA is traveling on the road surfaces of ISO level A, level B, and level C with a high velocity of over 70 km/h, the root mean square value of the driver's seat acceleration with the NSS-AP is also slowly increased and slower than that of the NSS-TMD. Moreover, the root mean square value of the driver's seat acceleration with the NSS-AP is also reduced in comparison with the NSS-TMD under the change of the total mass of the in-wheel-motor and the rotor's eccentricity. Thereby, the NSS-AP improves the EA's ride quality better than the NSS-TMD; and the NSS-AP should be used on the seat suspension of the EA to further enhance the ride quality.